Super Tax Deduction: Tax Incentives for Development of Human Resources Competencies - Made Laksmi Sena Hartini; Ni Luh Gede Mahayu Dicriyani (Journal of International Conference Proceedings (JICP), 2021)
Industrial Revolution 4.0 has had a huge and far-reaching impact, particularly on the employment sector, where robots and machines will eliminate many jobs in the world. Government commitment in improving the competence of Indonesian human resources is by providing tax incentives for businesses who carry out work practices, apprenticeships, and/or learning activities in the context of fostering and developing certain competency-based human resources called Super Tax Deduction. This study used a qualitative approach with literature research (library research) method. Based on the conducted study, the Super Deduction Tax can only have a significant impact on the company if it is balanced with the provision of additional gross income reductions and many requirements that must be met to be able to take advantage of Super Tax Deduction.